Growth of Zingiber zerumbet (L.) Smith as affected by different organic fertilizers and harvesting times - Munawer, Nurhidah; Shahari, Rozilawati (2018)
Zingiber zerumbet (L.) Smith or lempoyang has various application especially in pharmacological field. This study investigated effects of different organic fertilizers and harvesting times on growth of lempoyang grown at Pahang Matriculation College. The 9 treatment combinations were arranged in a randomized complete block design with five replications. Chemical analysis of soil and organic fertilizers were conducted. The morphological growth were regularly measured at 2 weeks interval. The interaction between organic fertilizers and harvesting times gave high significant (P<0.001) effect to tiller and leaf number, plant height and pseudo-stem diameter. Different organic fertilizers showed significant differences (p<0.05). Quail litter significantly produced the highest mean on leaf number (14.94a), tiller number (8.10a), height (33.50a) and pseudo-stem diameter (0.83a). Most parameters showed directly proportional to the time. The maximum height (34.62a) recorded in 150 days after transplanting (DAT) followed by 120 DAT (30.02b). Combination of goat manure with 150 DAT produced plants with the highest growth biometrics for leaf number, length of leaf 1, length of leaf blade 1-3, width of leaf blade 1 and 2. From the findings of this study, it can be concluded that application of quail litter and goat manure in combination with late harvest could enhanced the growth of Zingiber zerumbet.